FACTORS AFFECTING OF MUSCULOSKELETAL DISORDER’S (MSDS) COMPLAINTS ON THE DRIVERS OF GAJAH MADA PUBLIC TRANSPORTATION MEDAN - ferusgel, Agnes; Rahmawati, Nurul (Preventif : Jurnal Kesehatan Masyarakat, 2018)
Background & Objective: Musculoskeletal disorders complaints are complaints in the joints, ligaments andtendons which are caused because the muscles receive static loads repeatedly and continuously for a longtime. This study to determine the influencing factors nd musculoskeletal disorder's (MSDs) complaints onthe drivers of Gajah Mada public transportation Medan. Material and Method: The research design wasanalytical survey research method using cross sectional approach. The samples in this study were 30 peoplewho were the total population of public transport drivers. The data analysis using regression linear test.Result: The majority of the drivers are in the majority aged 52-59 years old at 30.0%. The 1-6 year workperiod is 30.0%. Work attitude in the medium category is 90%. Conclusion: There is an influence of age,years of service and work attitude towards musculoskeletal disorder’s complaints on Gajah Mada publictransport drivers Medan. It is also hoped that the driver will use the rest time to relax the muscles that aim tostretch the muscles so as not to cause muscle tension when working.